Editorial : Tropical Climate Variability and Change: Impacts in the Amazon - Jimenez, Juan C. (2019)
Vast amounts of data from satellites and ground-based systems, and improvements on modeling techniques, allows a better understanding of Earth processes and advances on climate science. The tropics play a key role on global climate processes, and the tropical forest is a sensitive biome in the global hydrological and carbon cycles. In particular, the Amazon region includes about one half of the world’s tropical forest, and relatively small change in Amazon forest dynamics have the potential to substantially affect the rate of climate change. This Research Topics focus on recent finding on the impacts of tropical climate variability and change over the Amazon ecosystem using satellite data, ground-based measurements or reanalysis climate data.